Non operative management of a patient with splenic trauma with angioembolisation after delayed presentation - Paul, Deepak; Thomas, Thomas K.; Babu, Dayananda; Janardhanan, Rajan; Christhudas, Ribin (International Surgery Journal, 2019)
Road traffic accidents are one of the most common causes of death in India. Those involved in RTA’s frequently suffer from solid organ injury, spleen being the second most common organ involved. Splenic injuries are associated with great deal of mortality and morbidity. Splenic injuries were classically treated with splenectomy but there has been a paradigm shift to non-operative management in recent times leading to splenic salvage and preservation of function of the spleen. This report is about a lady who was managed successfully with angioembolization in spite of the fact that the patient presented late after RTA.